دور منصات التواصل الاجتماعي في زيادة نشر المعارف العلمية لدى الاساتذة الجامعيين - - قروج الخادم; بوصوري براهيم; د/- مراح سميرة (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة: تهدف الدراسة الى الكشف عن دور منصات التواصل الاجتماعي في زيادة نشر المعارف العلمية لدى الاساتذة الجامعيين لغرض الحصول المعلومات؛ وقد استخدمنا المنهج الوصفي كما تم تطبيق الاستبيان كأداة لجمع البيانات وتم توزيعها على اساتذة كلية العلوم الانسانية والاسلامية والحضارة بجامعة الاغواط ولقد توصلت نتائج ان أغلب الأساتذة يستخدمون منصات التواصل الاجتماعي فينشر المعارف العلمية بين الاساتذة الجامعيين» وان الاساتذة يستخدمون منصات التواصل الاجتماعي في المشاركة في المجموعات والمنتديات الاكاديمية ونشر الابحاث والمقالات العلمية ومشاركة المواد الدراسية والمحاضرات مع الطلاب. الكلمات المفتاحية: منصات التواصل الاجتماعي, المعارف العلمية؛ الاساتذة الجامعيين. Study summary: The study aims to reveal the role of social media platforms in increasing the dissemination of scientific knowledge among university professors for the purpose of obtaining information. We used the descriptive approach, and the questionnaire was applied as a tool for collecting data, and it was distributed to professors of the Faculty of Humanities, Islamic Sciences, and Civilization at the University of Laghouat. Results were found that most professors use social media platforms to spread scientific knowledge among university professors, and that professors use social media platforms to participate in groups and forums. The academy publishes research and scientific articles and shares study materials and lectures with students. Keywords: social media platforms, scientific knowledge; University professors.
دراسة استطلاعية على عينة من اساتذة كلية العلوم الانسانية